Recent Patents on Biosafety Strategies of Selectable Marker Genes in Genetically Modified Crops - Jiang, Yiming; Hu, Xiaoning; Huang, Haiying (Recent Patents on Food, Nutrition & Agriculture, 2014)
Genetically modified crops (GMCs) have been planted world wide since 1990s, but the potential insecurity of selectable marker genes raises the questions about GMC safety. Therefore, several researches have been conducted on marker gene safety issues and recently several patents have been issued on this subject. There are two main approaches to achieve this goal: seeking the biosafety selectable marker and eliminating these insecure marker genes after transformation. Results show that these two systems are quite effective. Recent patents on the two ways are discussed in this review.
Keywords: marker genes-free